Epidemiological Study of Oral and Perioral Cancers in Isfahan - S. M. Razavit; S. Sajadiavit (Wolters Kluwer Medknow Publications, 2007)
Introduction: Despite the fact that oral and perioral cancers are not included in common cancers, they are of special importance for their impact on human morbidity and life quality. Awareness of the epidemiological characteristics of oral cancers allows for enhanced planning of timely and effective treatment in order to improve patients' life quality. The objective of the present study was to investigate the distributional patterns of oral and perioral malignancies in terms of age, gender, type, and location.Methods and Materials: 4553 oral biopsy specimens taken over 17 years (1988-2004) at the Department of Oral and Maxillo-Facial Pathology, Faculty of Dentistry, Isfahan University of Medical Sciences, were studied. Among these, 283 cases included oral malignant lesions. The age, gender, location, and type of malignancy data for these cases were recorded.Results: The results of this survey showed that commoner malignant oral lesions were epithelial lesions with 175 cases (62%), salivary lesions with 48 cases (17%), and hematogenic malignancies with 23 cases (9%). Squamous cell carcinoma, mucoepidermoid carcinoma, lymphoma, and osteosarcoma were the commoner malignant lesions in this area of the body. The mean age of patients was 52.2 years of old and the male to female ratio was found to be 1.3.Discussion: The present study showed that compared to the less common malignant lesions, the more common ones, i.e. epithelial and salivary lesions, show far more differences from those reported in previous studies. For example, compared to previous studies, the mean age for epithelial lesions was found to be less by one decade while the mean age for salivary gland lesions was found to be higher by one decade. Squamous cell carcinoma (SCC) was found to be the most common malignancy but its relative frequency was lower than that reported in previous studies. Moreover, differences were also observed in its anatomical distribution. Lip, salivary gland, and maxillary malignant lesions were less common than expected, which is probably due to their extra oral clinical characteristics. The results of the present study also showed that lesions with relatively lower frequencies are more similar to those reported in previous studies.